2019
DOI: 10.1177/0883073819876470
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome in Children:: A Prospective Follow-up Study

Abstract: Aim: To evaluate clinical and radiologic presentation, and neurologic outcome of pediatric posterior reversible encephalopathy syndrome (PRES). Patients and Methods: The study included 24 children (14 males and 10 females) diagnosed with PRES who were prospectively followed for 2 years. They were evaluated using Wechsler Intelligence Scale, electroencephalograph (EEG), and brain magnetic resonance imaging (MRI). Results: The mean age of the studied patients at the time of diagnosis of PRES was 6 years (±2.2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…However, in a 2018 study published by Li et al (25), in a total of 84 children with the thalassemia after conducting HSCT, 62 patients were male, and of the 11 PRES patients, 5 patients (45.4%) were male. In 2017, a study reported by Gaziev et al (18) showed that in children with hematological diseases after HSCT, the male-to-female ratio was 23:8, and in pediatric cancers treated with chemotherapy, the male-to-female ratio was 14 (58%):10 (41.7%) among 24 pediatric patients with PRES (7). In contrast, a case-control study composed of acute lymphoblastic leukemia (ALL) pediatric patients that also underwent chemotherapy concluded that maleto-female ratio was 25 (48%):27 (51%), and the age group 10.0-17.0 years, or older children were prone to developing PRES (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a 2018 study published by Li et al (25), in a total of 84 children with the thalassemia after conducting HSCT, 62 patients were male, and of the 11 PRES patients, 5 patients (45.4%) were male. In 2017, a study reported by Gaziev et al (18) showed that in children with hematological diseases after HSCT, the male-to-female ratio was 23:8, and in pediatric cancers treated with chemotherapy, the male-to-female ratio was 14 (58%):10 (41.7%) among 24 pediatric patients with PRES (7). In contrast, a case-control study composed of acute lymphoblastic leukemia (ALL) pediatric patients that also underwent chemotherapy concluded that maleto-female ratio was 25 (48%):27 (51%), and the age group 10.0-17.0 years, or older children were prone to developing PRES (2).…”
Section: Discussionmentioning
confidence: 99%
“…The patients did not have any other PRES attacks during the follow-up period. Development of epilepsy as a sequela was observed in other studies: Datar et al, 16 2.4%; Sha et al, 18 2.6%; Heo et al, 19 3.9%; Darwish et al, 26 8;3%; Endo et al, 15 25%. The longest median follow-up in these studies was 3.2 years.…”
Section: Discussionmentioning
confidence: 53%
“…In the pediatric age group, neoplastic, renal disorders and hematopoietic stem cell transplantation represent the main disorders associated with PRES [11] . Chemotherapeutic drugs, immunosuppressants, and hypertension appear to be the main risk factors for the development of pediatric PRES [11] . A retrospective study has suggested no association between sepsis and PRES in children [12] .…”
Section: Discussionmentioning
confidence: 99%